Linguistik Terapan dalam Studi Bahasa Arab: Teori, Metodologi, dan Aplikasi Pedagogis - Wiwin; Nisa, Khoirun; Mursalati 'Aini, Nancy; Riyadi, Sugeng; Susiawati, Iis (INCARE, International Journal of Educational Resources, 2025)
This article discusses the role of applied linguistics (Ilmu Lughah al-Ta?b?q?) in the study of the Arabic language, focusing on its theoretical foundations, methodologies, and pedagogical applications. The study emphasizes how applied linguistics provides tools for bridging language theory and practical teaching. By exploring approaches such as contrastive analysis, error analysis, discourse analysis, and communicative competence, this paper highlights the significance of applied linguistics in addressing real problems in Arabic teaching and learning. Methodologically, this research adopts a qualitative-descriptive approach, reviewing classical and modern perspectives to show the evolution of Arabic linguistics from a traditional grammatical orientation to contemporary communicative pedagogy. Findings reveal that applied linguistics enables educators to design curricula, teaching strategies, and assessments that are more relevant to the learners’ needs. It also underlines the importance of integrating modern technologies, corpora, and second-language acquisition theories into Arabic pedagogy. The study concludes that applied linguistics is indispensable in modernizing Arabic language education while maintaining its classical depth and cultural identity.